Cognitive Impairments in Fibromyalgia Syndrome: Associations With Positive and Negative Affect, Alexithymia, Pain Catastrophizing and Self-Esteem - Galvez-Sánchez, Carmen M.; Reyes del Paso, Gustavo A.; Duschek, Stefan (Frontiers in Psychology, 2018)
Abstract Fibromyalgia syndrome (FMS) is a chronic condition characterized by widespread pain accompanied by symptoms like depression, anxiety, sleep disturbance and fatigue. In addition, affected patients frequently report cognitive disruption such as forgetfulness, concentration difficulties or mental slowness. Though cognitive deficits in FMS have been confirmed in various studies, not much is known about the mechanisms involved in their origin. This study aimed to investigate the contribution of affect-related variables to cognitive impairments in FMS. For this purpose, 67 female FMS patients and 32 healthy control subjects completed a battery of cognitive tests measuring processing speed, attention, visuospatial and verbal memory, cognitive flexibility and planning abilities. In addition, participants completed self-report questionnaires pertaining to positive and negative affect, alexithymia, pain catastrophizing and self-esteem. Clinical characteristics including pain severity, symptoms of depression and anxiety, insomnia and fatigue were also assessed. FMS patients showed markedly poorer performance than healthy controls in all of the cognitive domains assessed, in addition to greater levels of depression, anxiety, negative affect, alexithymia and pain catastrophizing, and lower self-esteem and positive affect. In exploratory correlation analysis in the FMS sample, lower cognitive performance was associated with higher pain severity, depression, anxiety, negative affect, alexithymia and pain catastrophizing, as well as lower self-esteem and positive affect. However, in regression analyses, pain, self-esteem, alexithymia, and pain catastrophizing explained the largest portion of the variance in performance. While interference effects of clinical pain in cognition have been previously described, the present findings suggest that affective factors also substantially contribute to the genesis of cognitive impairments. They support the notion that affective disturbances form a crucial aspect of FMS pathology, whereas strategies aiming to improve emotional regulation may be a beneficial element of psychological therapy in the management of FMS. Keywords: Fibromyalgia, chronic pain, cognitive impairment, affective regulation, alexithymia, pain catastrophizing, self-esteem